Phylogeographic, genomic, and meropenem susceptibility analysis of Burkholderia ubonensis. - Erin P Price; Derek S Sarovich; Jessica R Webb; Carina M Hall; Sierra A Jaramillo; Jason W Sahl; Mirjam Kaestli; Mark Mayo; Glenda Harrington; Anthony L Baker; Lindsay C Sidak-Loftis; Erik W Settles; et al. (PLoS Neglected Tropical Diseases)
The bacterium Burkholderia ubonensis is commonly co-isolated from environmental specimens harbouring the melioidosis pathogen, Burkholderia pseudomallei. B. ubonensis has been reported in northern Australia and Thailand but not North America, suggesting similar geographic distribution to B. pseudomallei. Unlike most other Burkholderia cepacia complex (Bcc) species, B. ubonensis is considered non-pathogenic, although its virulence potential has not been tested. Antibiotic resistance in B. ubonensis, particularly towards drugs used to treat the most severe B. pseudomallei infections, has also been poorly characterised. This study examined the population biology of B. ubonensis, and includes the first reported isolates from the Caribbean. Phylogenomic analysis of 264 B. ubonensis genomes identified distinct clades that corresponded with geographic origin, similar to B. pseudomallei. A small proportion (4%) of strains lacked the 920kb chromosome III replicon, with discordance of presence/absence amongst genetically highly related strains, demonstrating that the third chromosome of B. ubonensis, like other Bcc species, probably encodes for a nonessential pC3 megaplasmid. Multilocus sequence typing using the B. pseudomallei scheme revealed that one-third of strains lack the "housekeeping" narK locus. In comparison, all strains could be genotyped using the Bcc scheme. Several strains possessed high-level meropenem resistance (≥32 μg/mL), a concern due to potential transmission of this phenotype to B. pseudomallei. In silico analysis uncovered a high degree of heterogeneity among the lipopolysaccharide O-antigen cluster loci, with at least 35 different variants identified. Finally, we show that Asian B. ubonensis isolate RF23-BP41 is avirulent in the BALB/c mouse model via a subcutaneous route of infection. Our results provide several new insights into the biology of this understudied species.